Conservation implications of genetic structure in the narrowest endemic quillwort from the Eastern Amazon. Issue 15 (13th July 2021) - Dalapicolla, Jeronymo; Alves, Ronnie; Jaffé, Rodolfo; Vasconcelos, Santelmo; Pires, Eder Soares; Nunes, Gisele Lopes; Pereira, Jovani Bernardino de Souza; Guimarães, José Tasso F.; Dias, Mariana C.; Fernandes, Taís Nogueira; Scherer, Daniela; dos Santos, Fernando Marino Gomes; et al.
Abstract: The quillwort Isoëtes cangae is a critically endangered species occurring in a single lake in Serra dos Carajás, Eastern Amazon. Low genetic diversity and small effective population sizes ( N e ) are expected for narrow endemic species (NES). Conservation biology studies centered in a single species show some limitations, but they are still useful considering the limited time and resources available for protection of species at risk of extinction. Here, we evaluated the genetic diversity, population structure, N e, and minimum viable population (MVP) of I .  cangae to provide information for effective conservation programs. Our analyses were based on 55 individuals collected from the Amendoim Lake and 35, 638 neutral SNPs. Our results indicated a single panmictic population, moderate levels of genetic diversity, and N e in the order of thousands, contrasting the expected for NES. Negative FIS values were also found, suggesting that I .  cangae is not under risk of inbreeding depression. Our findings imply that I .  cangae contains enough genetic diversity to ensure evolutionary potential and that all individuals should be treated as one demographic unit. These results provide essential information to optimize ex situ conservation efforts and genetic diversity monitoring, which are currently applied to guide I .  cangae conservation plans. Abstract : The quillwort Isoëtes cangae is a critically endangered species occurring in a single lake in Serra dos Carajás, Eastern Amazon. To provide information for effective conservation programs, we evaluated its genetic diversity and population structure using neutral SNPs. Our results indicated a single panmictic population, moderate levels of genetic diversity, and effective population size in the order of thousands, contrasting to the expected for NES.